2022
DOI: 10.3390/cells11060975
|View full text |Cite
|
Sign up to set email alerts
|

Thyroidal Transcriptomic Profiles of Pathoadaptive Responses to Congenital Hypothyroidism in XB130 Knockout Mice

Abstract: Congenital hypothyroidism is a genetic condition in which the thyroid gland fails to produce sufficient thyroid hormone (TH), resulting in metabolic dysfunction and growth retardation. Xb130−/− mice exhibit perturbations of thyrocyte cytoskeleton and polarity, and develop postnatal transient growth retardation due to congenital hypothyroidism, leading ultimately to multinodular goiter. To determine the underlying mechanisms, we performed transcriptomic analyses on thyroid glands of mice at three age points: we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Thus, the identification of therapeutic targets of IR injury for pharmacological intervention is a major research goal in transplantation medicine. In the present study, we found that the transcriptomic profile of human lung epithelial cells exposed to simulated transplant conditions had a signature profile like those found in clinical human lung transplants [13] and in the thyroid glands of mice with congenital hypothyroidism [18]. This prompted us to investigate whether incorporating THs into the standard clinical lung preservation solution could protect against IR injury.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Thus, the identification of therapeutic targets of IR injury for pharmacological intervention is a major research goal in transplantation medicine. In the present study, we found that the transcriptomic profile of human lung epithelial cells exposed to simulated transplant conditions had a signature profile like those found in clinical human lung transplants [13] and in the thyroid glands of mice with congenital hypothyroidism [18]. This prompted us to investigate whether incorporating THs into the standard clinical lung preservation solution could protect against IR injury.…”
Section: Discussionmentioning
confidence: 60%
“…A recent bioinformatics study showed that in the thyroid tissue of mice with congenital hypothyroidism, there is a downregulation of gene clusters related to cellular metabolism, followed by an up-regulation of genes related to inflammation [18]. THs are critical for many essential cellular functions, especially metabolism [19] and protein synthesis [20].…”
Section: Adding T3 or T4 To The Preservation Solution Enhances Cell V...mentioning
confidence: 99%